Laugh and Learn: Evaluating from Studentsâ Perspective of Humor Used in English Class - Fata, Ika Apriani; Komariah, Endang; Irfandy, Irfandy (AT-TALIM, 2018)
Laughter is an easily reachable way that can be used to erase barriers of communication for educational purposes. The purpose of this paper is to seek out studentsâ perception of humor added in teaching English and how that humor influenced studentsâ engagement in English classroom activity. This study employs research instrument of questionnaire and observation concepts through qualitative design. There are 78 students of multi-background: gender, level of intelligence and social background as research participants. These backgroundsareintended to obtain objective perception of the students. The findings revealed that the majority of students believed the teacherâs humor could prevent them from feeling stress of learning English, develop a better relationship between teacher and students, help them remember and understand the lesson, encourage them to be more active in the classroom and ease them in learning English. However there are some obstacles to overcome during humor application that apparently the English teachers need to build a good relationship and mutual trust with students and understand studentsâ interests, likes and dislikes prior to applying humor, so that the humor would be more likely to be welcomed and it would not cause emotional and psychological impact such as bullying and etc for the students.